ARMENIA AND GEORGIA: PROBLEMS AND PROSPECTS - MINASIAN, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2012)
Relations between Armenia and Georgia go back many centuries into the history of these two neighboring nations. The recent history of their relations as two post-Soviet newly independent states is only two decades old, which means that certain problems have not yet been resolved. Both countries have to cope with political, ethnopolitical, economic, linguistic, and religious problems; the situation in both countries is further complicated by the far from simple processes of nation-building and the countries’ involvement in bloody ethnopolitical conflicts in the Caucasus. This has inevitably affected the political and socioeconomic development of both Armenia and Georgia. Here I am going to assess the general dynamics, present state, possible prospects, and potential problems in Armenian-Georgian relations. I have paid particular attention to the main parameters of their relations in the economic, communication, political, military, cultural, educational, and humanitarian spheres, to say nothing of an especially important aspect regarding the Russian factor in Armenian-Georgian relations and the situation in Samtskhe-Javakheti, an administrative region of Georgia with a predominantly Armenian population.